2003
DOI: 10.1051/apido:2003040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some essential oils for the control and prevention of American Foulbrood disease in honey bees

Abstract: -American Foulbrood (AFB), caused by the spore-forming bacterium Paenibacillus larvae larvae, is the most serious disease of honeybees. Laboratory and field trials were conducted to evaluate the effectiveness of essential oils from savory, thyme, lemon-grass, and oregano, and blends of lemon-grass + thyme; lemon-grass + thyme + oregano + basil, and lemon-grass + thyme + basil in preventing and controlling infections of AFB in Apis mellifera colonies. The principal components of the essential oils used were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…The concentrations of the natural compounds in the candy were chosen on the basis of preliminary tests and previous research (Albo et al, 2003;Maistrello et al, 2003) and are shown in Table I. The candy, contained in a 3 cm diameter Petri dish (9 g), was positioned upside-down on a 1 cm diameter hole on top of the cage.…”
Section: Bee Susceptibility and Diet Preference Experimentsmentioning
confidence: 99%
“…The concentrations of the natural compounds in the candy were chosen on the basis of preliminary tests and previous research (Albo et al, 2003;Maistrello et al, 2003) and are shown in Table I. The candy, contained in a 3 cm diameter Petri dish (9 g), was positioned upside-down on a 1 cm diameter hole on top of the cage.…”
Section: Bee Susceptibility and Diet Preference Experimentsmentioning
confidence: 99%
“…Plant essential oils have been studied for their antimicrobial activity against microorganisms, including many pathogens (Dorman and Deans, 2000;Delaquis et al, 2002). In vitro antibacterial, antifungical and miticide activity of some essential oils have shown effective results in the control of bee pests (Calderone and Shimanuki, 1994;Alippi et al, 1996;Floris et al, 1996;Bazzoni and Floris, 1999;Albo et al, 2001Albo et al, , 2003Ruffinengo et al, 2002Ruffinengo et al, , 2005Ruffinengo et al, , 2006Dellacasa et al, 2003;Eguaras et al, 2005;Fuselli et al, 2006Fuselli et al, , 2007 offering a natural desirable alternative to antibiotics and other synthetic chemical substances.…”
Section: Introductionmentioning
confidence: 99%
“…American foulbrood is considered a global threat to apiculture because the etiologic agent produces environmentally stable spores which are very virulent, and resistant to Antimicrobial activity and toxicity of B. thyrsoides heat, to desiccation, and to disinfectants (Genersch, 2010;Boligon et al, 2013a). Products derived from plants, such as propolis (Bastos et al, 2008;Mihai et al, 2012), essential oils (Albo et al, 2003;Santos et al, 2012); and extracts of Myrtus communis L., Eucalyptus dunnii (Maiden), Rosmarinus officinalis L., Zingiber officinale (Roscoe), Scutia buxifolia (Reissek), among other species (Flesar et al, 2010;Boligon et al, 2013a) were previously investigated and exhibited a growth-inhibitory effect against AFB. Buddleja is a genus with pan tropical distribution that occurs in South Asia, Africa, and America (Mahlke et al, 2009).…”
mentioning
confidence: 99%